2015
DOI: 10.1021/acs.jpcc.5b04274
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Colloidal Stabilization of Oxidized Nanocarbons in the Presence of Polymers: Obtaining Highly Stable Colloids in Physiological Media

Abstract: There are successful protocols for dispersing carbon nanotubes and graphene oxide in physiological media by using biocompatible polymers, which enable their use in nanomedicine. However, there is not a clear understanding regarding the mechanisms of the colloidal stabilization manifested (i.e., electric, steric or electrosteric or through depletion forces). Here we show that the manifestation of a particular mechanism of stabilization for oxidized carbon nanotubes (CNTs) and graphene oxide (GO) in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 62 publications
5
13
0
Order By: Relevance
“…Table 2 shows the respective quantities found for each group. Similar results have been reported in the literature for other samples of graphene oxide (Faria et al 2012;Padovani et al 2015).…”
Section: Resultssupporting
confidence: 92%
“…Table 2 shows the respective quantities found for each group. Similar results have been reported in the literature for other samples of graphene oxide (Faria et al 2012;Padovani et al 2015).…”
Section: Resultssupporting
confidence: 92%
“…The manifestation of attractive or repulsive depletion forces depends mostly on the polymer concentration. [38][39][40] When mixed with MSNs in the NaCl 0.9% solution, it was observed that at 3 wt% PF127 leads to a destabilization of the MSNs sols (i.e., colloidal suspension), whereas at 5 wt% (or above) the same polymer is able to stabilize MSN ( Fig. SM-3; ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…The manifestation of both kinds of interactions (short-and long-range; i.e., adsorption and depletion forces) was previously observed for PF127 (ref. 40) and also for polyethylene glycol. 39 Therefore, as in the hybrid systems the PF127 concentration is 18 wt% (to form hydrogels), much higher than the observed threshold for repulsive depletions forces to occur, this polymer will act as an initial stabilizing agent for MSNs from the time of injection up to a possible formation of the protein capping (i.e., corona effect), resulted from the adsorption of proteins on the MSNs surface, [41][42][43] which are also able to provide colloidal stabilization for MSNs.…”
Section: Mesoporous Silica Nanoparticles (Msns)mentioning
confidence: 99%
“…In the particular case of biogenic AgNPs (Ag-Glutinis and Ag-Mucilaginosa), the colloidal stabilization by steric/electrosteric mechanisms must also be accounted due to the presence of macromolecules in the protein corona. 8,48 Assessment of the AgNPs coatings at multiple scales with LF X-ray imaging…”
Section: Characterization Of Synthetic and Biogenic Agnpsmentioning
confidence: 99%